EMPLOYEE PERFORMANCE IN TERMS OF MOTIVATION, COMPETENCE, DISCIPLINE AND WORK ENVIRONMENT (Case Study at the Investment and One-Stop Integrated Service Service Office of Klaten Regency) - Wandansari Wandansari; Istiatin Istiatin; Sudarwati Sudarwati; Agus Gunawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research was used to determine employee performance in terms of motivation, competence, discipline, and work environment at the Investment Office and One-Stop Integrated Services of Klaten Regency. The population and samples in this study were 33 respondents who were all employees who worked in the Klaten Regency Investment and One-Stop Integrated Services Office. The data analysis technique in this study is multiple linear regression using SPSS software. Before analyzing the data with multiple linear regression, instrument tests and classical assumption tests have been carried out first in concluding the data of this study. From the research carried out, the adjusted R Square (R²) value of 0.857 or 85.7% was obtained. The determination or contribution of variables of motivation, competence, discipline and work environment to the performance of employees in the Investment and One-Stop Integrated Services Office of Klaten Regency was 85.7%. The rest contributed only 14.3% of other variables of professionalism, workload, education and others.